Suicide assisted by two Swiss right-to-die organisations. Issue 11 (30th October 2008) - Fischer, S; Huber, C A; Imhof, L; Mahrer Imhof, R; Furter, M; Ziegler, S J; Bosshard, G
Abstract : Background: In Switzerland, non-medical right-to-die organisations such as Exit Deutsche Schweiz and Dignitas offer suicide assistance to members suffering from incurable diseases. Objectives: First, to determine whether differences exist between the members who received assistance in suicide from Exit Deutsche Schweiz and Dignitas. Second, to investigate whether the practices of Exit Deutsche Schweiz have changed since the 1990s. Methods: This study analysed all cases of assisted suicide facilitated by Exit Deutsche Schweiz (E) and Dignitas (D) between 2001 and 2004 and investigated by the University of Zurich's Institute of Legal Medicine (E: n = 147; D: n = 274, total: 421). Furthermore, data from the Exit Deutsche Schweiz study which investigated all cases of assisted suicide during the period 1990–2000 (n = 149) were compared with the data of the present study. Results: More women than men were assisted in both organisations (D: 64%; E: 65%). Dignitas provided more assistance to non-residents (D: 91%; E: 3%; p = 0.000), younger persons (mean age in years (SD): D: 64.5 (14.1); E: 76.6 (13.3); p = 0.001), and people suffering from fatal diseases such as multiple sclerosis and amyotrophic lateral sclerosis (D: 79%; E: 67%; p = 0.013). Lethal medications were more often taken orally in cases assisted by Dignitas (D: 91%; E: 76%; p = 0.000). The number of women and the proportion of older people suffering from non-fatal diseases among suicides assisted by Exit Deutsche Schweiz has increased since the 1990s (women: 52% to 65%, p = 0.031; mean age in years (SD): 69.3 (17.0) to 76.9 (13.3), p = 0.000), non-fatal diseases: 22% to 34%, p = 0.026). Conclusions: Weariness of life rather than a fatal or hopeless medical condition may be a more common reason for older members of Exit Deutsche Schweiz to commit suicide. The strong over-representation of women in both Exit Deutsche Schweiz and Dignitas suicides is an important phenomenon so far largely overlooked and in need of further study.